(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
Review of the doctoral thesis of Denis Zamignani (2007), submitted to the graduate program of the Institute of Psychology, University of São Paulo and directed by Prof. Sonia Beatriz Meyer. The work is named “Developing a multidimensional system for the categorization of behaviors in the therapeutic interaction. “ Zamignani conducts a process research using direct observation of the psychotherapy session for the identification and categorization of behaviors. The main objective of the thesis is the development of a categorization system of behaviors of the therapist and client to study the characteristics of the therapeutic interaction and its relation to the quality of psychotherapy.